Depression in Elite Athletes - Interplay between neuroendocrine disturbances, immune-inflammatory responses, and disturbed sleep: A Narrative Review - Chawryło, Aneta; Łupina-Romaniuk, Marcela; Kołodziejczyk , Julia; Pietraś, Paulina; Piecuch, Dominika; Pietrzak, Maria; Oleksińska, Karolina; Świetlicka , Gabriela; Stolarczyk , Michał; Pracoń, Karolina (Quality in Sport, 2026)
Background. Depression in mental health is an important issue in elite athletes, with significant consequences for physical performance and physiological adaptation. Notwithstanding the perception of athletes as robust individuals, recent findings show that higher performance athletes report symptoms of depression at least at or above the general population levels.It can be a combination of competitive pressure, overtraining, injury and a career change.. Aim.The aim of this study was to present the current state of knowledge on the effects of Depression in Elite Athletes- its Impact on Bodily Functioning and The Capacity for Physical Exertion Material and Methods. A narrative review was conducted using databases PubMed and full-text articles available in PubMed Central (PMC) and Web of Science covering publications from 2000 to 2025. Terms used for search "depression", "elite athletes", "mental health" Results. Research indicates that depression now represents a significant health concern among athletes.Indeed, gender, sport type, and age seem to moderate these outcomes with higher symptom rates seen in female and in individual-sport athletes.Elite athlete depression not only jeopardises psychological functioning but also induces strong physiological disruptions causing adverse effects on athletic performance. The reasons for this complex interplay include neuroendocrine regulation, immunity and sleep quality. Conclusion. Depression in elite athletes is a common and often complex disorder that has been shown to have major impact upon mental health and sport performance. The incorporation of the physiological and psychological perspectives in this review illustrates how depression deserves to come to terms in athlete holistic management as part of the holistic approach of mental health services.